Karakteristik Geomorfologi Daerah Posso Kabupaten Gorontalo Utara dan Sekitarnya - Budiyansyah Harun; Yayu Indriati Arifin; Intan Noviantari Manyoe (Jambura Geoscience Review, 2022)
The landforms in the Gorontalo area are only limited to the physiographic division of Gorontalo. Therefore, this research aims to analyze the geomorphological characteristics of the research area to obtain detailed data that can be used as basic data for the theoretical purposes of Gorontalo geomorphology and disaster applications. The method used in this research is field observation and visual interpretation using satellite imagery, namely GeoEye (GoogleEarth) and Digital Elevation Model. Data analysis was carried out in the form of an analysis of the geomorphological condition of the research area supported by the results of image interpretation—determination of geomorphological units using the Van Zuidam classification. The results showed that the geomorphology of the study area consisted of six geomorphological units: structural hills, volcanic hills, denudational hills, denudational plains, fluvial plains, and marine plains. The morphography and morphometry of the research area are hilly, lowland, and coastal plains generally located at an altitude of 0-393 masl with slopes ranging from flat to extremely steep with a sloping pattern. The morphology of the landform units in the study area starts from the Early Miocene to the Holocene in the form of magmatism, volcanism, and exogenous processes. The presence of geological structures in the form of fractures and faults in geomorphological units and the influence of exogenous processes on landforms can be a reference in mapping the direction of mitigation in the research area, theoretically and practically.